Clinical features and computed tomography findings of retrobulbar disease in cats - Hasegawa, Kristen; Vincek, Anna; Evenhuis, Janny V.; Goldschmidt, Stephanie; Soltero-Rivera, Maria; Vapniarsky, Natalia; Good, Kathryn; Gutierrez, Claudio J.; Arzi, Boaz (Frontiers in Veterinary Science, 2026)
The objective of this study was to describe the clinical features and computed tomography (CT) findings of cats affected with retrobulbar disease. The medical records of 37 client-owned cats diagnosed with retrobulbar disease between the years 2009–2024 were reviewed. Clinical information, signalment, the presenting specialty service, clinical signs, diagnostic results, treatment, and outcomes were documented. CT features of retrobulbar disease as well as cytology and histopathology were reviewed. Fifteen cats (40.5%) were diagnosed with primary disease in the retrobulbar space and 22 cats (59.5%) were diagnosed with secondary retrobulbar disease. Out of the 15 cats with primary retrobulbar disease, 9 were diagnosed with neoplasia, 3 were diagnosed with an infectious/inflammatory process, 2 were traumatic in origin, and 1 cat had a cyst. Of the 22 cats with secondary retrobulbar disease, 21 cats were diagnosed with neoplasia and 1 cat was diagnosed with an infectious disease. CT findings of orbital osteolysis and reduction of retrobulbar fat were significantly associated with neoplasia. Survival outcomes for cats diagnosed with a primary retrobulbar infectious/inflammatory disease were significantly better than for those diagnosed with primary or secondary retrobulbar neoplasia. This study found that neoplasia is the most common primary and secondary retrobulbar disease in cats. Due to the significantly different prognostic implications between cats with primary infectious/inflammatory retrobulbar disease, primary neoplasia and secondary neoplasia, we also confirmed that CT is an essential part of diagnosis and characterization of the extent of the disease, and that additional diagnostics such as histopathology, cytology, culture and susceptibility, or fungal cultures are needed to further support and guide treatment options. Finally, cats that present with either primary infectious/inflammatory or traumatic retrobulbar disease carry favorable prognosis with either medical or surgical intervention.